Enhancing Social and Educational Awareness through Ramadan-Based Community Service in Kuningan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This study reports the implementation of a community service program conducted in Kertawangunan Village, Kuningan Regency, during Ramadan 2026. The program aimed to enhance social awareness, character education, and public understanding of education, health, and religious values. A participatory, educational, and religious approach was employed through various activities, including anti-bullying socialization, teaching in madrasas, social services, free health checks, and religious competitions. The results indicate increased student awareness of bullying prevention, improved learning motivation in madrasas, and strong community participation in social and religious activities. The program also strengthened social solidarity and provided experiential learning for students. These findings suggest that integrated community service programs can effectively promote social, educational, and spiritual development in rural communities.